Reimagining management education: Ideas, insights and future actions - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 2016)
A number of recent events have been important in examining the future success of management education. The first is the business education, "crowdsourcing" Jam (Carlile et al.,2016), designed and implemented by the Questrom School of Business at the Boston University. This Jam was co-sponsored by EFMD, GMAC and AACSB as well as a range of business and management stakeholders such as Johnson and Johnson, Merck, Financial Times (FT), IBM, Santander, Fidelity, PWC and E&Y. The second is the AACSB visioning process summarised in the recent document "Envisioning The Future" produced by AACSB (AACSB,2016) on the occasion of the 100th anniversary on its foundation in 1916. Both studies were stimulated by the proposition that there has been little radical, innovative curriculum change in management education over the last 50 years. Indeed the dominant logic in the field, outlined in the influential the Gordon and Howell (1959) report on management education, from a US perspective, has largely prevailed. However, critics such as Henry Mintzberg (2004), have argued that we need to emphasise and teach the art of management alongside the appropriate set of analytical skills and tools to address management problems that often dominate management courses.